Geometric Coefficients Modifications of Surface Non-Treated Seven-Perforated Nitrocellulose Powder (Advances in Military Technology, 2022)
Calculating of the interior ballistics characteristics using seven-perforated nitrocellulose powder in cartridge assemblies can be used in special techniques and in special projectile sets. Accuracy of interior ballistics characteristics calculations influences construction solutions of special techniques and ammunition; main utilization is in armed forces special techniques and ammunition for country defence. Originally derived relations make geometric coefficients solution of non-treated seven-perforated powder more accurate and easier to use.
Keywords: interior ballistics; interior ballistics characteristics; ammunition; gun; nitrocellulose powder